До характеристики умови відшкодування шкоди, завданої роботодавцем - Мельник, В. В.; Melnyk, V. V. (Держава та регіони. Серія: Право. – 2020. – № 3 (69), т. 3. – С. 46-51, 2020)
Розглянуто зміст умов відшкодування шкоди завданої роботодавцем. Здійснено класифікацію умов відшкодування шкоди завданої роботодавцем працівнику. Акцентовано увагу на тому, що окреслені у статті умови досить розмито відображені у нормах чинного законодавства, а відтак, їх доцільно змістовно розкрити у майбутньому Трудовому кодексі України.

The relevance of the article lies in the fact that the analysis of the scientific views of scientists and law enforcement practice shows that the existing labor law regulation of compensation for damage in Ukraine does not have a complete and complete form and needs significant refinement both in the formal (systematization) and meaningful sense. Streamlining the researched legislation, eliminating gaps and other deficiencies in its content is a necessary condition for ensuring highquality legal regulation of damage compensation. In addition, an important problematic issue that needs to be resolved is the determination of the terms of compensation for damage caused by the employer. The list of conditions for indemnifying the employee is quite broad, and therefore it is most expedient to divide them into three large groups. The purpose of the article is to reveal the essence and content of the terms of compensation for damage caused by the employer. In the article, based on the analysis of the scientific views of scientists and the norms of the current legislation of Ukraine, the classification of conditions for compensation for damage caused by the employer to the employee was carried out. Attention is focused on the fact that the conditions outlined in the article are rather vaguely reflected in the norms of the current legislation, and therefore, they should be meaningfully disclosed in the future Labor Code of Ukraine. It was emphasized that the issue of conditions for compensation for moral damage caused by the employer is still unresolved. It was concluded that the norms of the current legislation provide for a fairly wide list of conditions, in the presence of which the employer may be obliged to compensate the employee. At the same time, the specified conditions are rather vaguely reflected in the norms of the current legislation, and therefore, it is expedient to disclose them meaningfully in the future Labor Code of Ukraine, the adoption of which, at the moment, is quite urgent. In our opinion, the legislator needs to pay special attention to the issue of the conditions for indemnification of moral damages to the employee, because today it remains actually unsettled. The legislative consolidation and expansion of the conditions for compensation of damage by the employer to the employee is an important guarantee of ensuring and observing the rights, freedoms and interests of the latter.

Рассмотрено содержание условий возмещения вреда, причиненного работодателем. Осуществлена ​​классификация условий возмещения вреда, причиненного работодателем работнику. Акцентировано внимание на том, что указанные в статье условия достаточно размыто отражены в нормах действующего законодательства, а значит, их целесообразно содержательно раскрыть в будущем Трудовом кодексе Украины.
To characterize the condition of compensation for damage caused by the employer
Keywords: правове регулювання; legal regulation; правовое регулирование; відшкодування шкоди; reparation; возмещение вреда; працівник; employee; работник; роботодавець; employer; законодавство; legislation; законодательство